Arctic Madness The Anthropology of a Delusion - Déléage, Pierre (HAU Books, 2020)
The French missionary-linguist Émile Petitot (1838-1916) spent twenty years near the Arctic Circle in Canada, publishing numerous works on First Nations languages and practices. Over time, however, he descended into delirium and began to summon imaginary persecutions, pen improbable interpretations of his Indigenous hosts, and burst into schizoid fury. Delving into thousands of pages in letters and memoirs that Petitot left behind, Pierre Déléage has reconstructed the missionary's tragic story. He takes us on a gripping journey into the illogic and hyperlogic of a mind entranced with Indigenous peoples against the backdrop of repressive church policies and the emergent social sciences of the nineteenth century. Apocalyptic visions from the Bible and prophetic movements among First Nations peoples merged in the missionary's deteriorating psyche, triggering paroxysms of violence against his colleagues and himself. Whoever wishes to understand the contradictions of living between radically different societies will find this anthropological novella hard to put down.